Determining the in vitro susceptibility of tebipenem, an oral carbapenem, against third-generation cephalosporin-resistant Escherichia coli and Klebsiella pneumoniae isolated from bloodstream infections. Issue 5 (30th September 2022) - Ranasinghe, Ama; Henderson, Andrew; Cottrell, Kyra; Tan, Cindy S E; Burnard, Delaney; Kato, Hideo; Paterson, David L; Harris, Patrick N A
Abstract: Background: Antimicrobials for bloodstream infections due to ESBL- and AmpC-producing Escherichia coli and Klebsiella pneumoniae are significantly limited due to widespread antimicrobial resistance. Tebipenem, an oral carbapenem, exhibits stability against these resistance mechanisms and may prove an attractive alternative. Methods: The in vitro susceptibility of tebipenem was assessed against previously whole-genome sequenced ESBL- and AmpC-producing E. coli (274 isolates) and K. pneumoniae (42 isolates) derived from bloodstream infections using broth microdilution testing. Resulting tebipenem MICs were compared with those of other carbapenems previously tested against the isolate collection. Tebipenem activity was also compared against those isolates expressing co-resistance to the common oral antibiotics ciprofloxacin and trimethoprim/sulfamethoxazole. Results: The tebipenem MIC90 value was found to be 0.03 mg/L for E. coli and 0.125 mg/L for K. pneumoniae . For E. coli, the tebipenem MIC90 value was equivalent to that of meropenem, 2-fold lower than that of doripenem, and 8-fold and 4-fold lower than that of imipenem and ertapenem, respectively. For K. pneumoniae, the tebipenem MIC90 value was 2-fold higher than that of meropenem, equivalent to that of doripenem, and 4-fold and 2-fold lower than that of imipenem and ertapenem, respectively. Tebipenem MICs were also unaffected by the expression of co-resistance to ciprofloxacin and trimethoprim/sulfamethoxazole. Conclusions: The in vitro activity of tebipenem was unaffected by the production of ESBL and AmpC enzymes. Tebipenem also retained its activity against those isolates expressing co-resistance to ciprofloxacin and trimethoprim/sulfamethoxazole. These findings therefore highlight tebipenem as a potential option for the treatment of invasive MDR infections.